Modeling transition diffusive - non diffusive transport in a turbid media and application to time-resolved reflectance - Di Rocco, Hector Omar (2013)
In this work a generalized solution for the photon density is proposed and applied to two types of experiments in turbid media carried out in the last years. Both involve small typical distances, where it is known that the diffusion approximation ceases to be valid. In one case, the use of time-resolved reflectance at small or null source-detector separation using fast single photon gating to localize small inhomogeneities embedded in diffusive media has been proposed. In other type of experiments, it is addressed the transition between the ballistic and the diffusive regimes, measuring the transmitted light within a relatively narrow solid angle. The model proposed here corroborates the importance of the solid angle of the measurement device in order to see the ballistic photons, and the given generalized solution provides valid answers to problems posed by the mentioned experiments. Furthermore, it permits the description of diffusive photons when the absorption coefficient is relatively high, where the diffusion approximation is not valid.